Justice - Salane, Jeffrey (Scholastic Press, 2015)
"M Freeman thought she had finally found a place where she belonged: the Lawless School, where the children of master criminals trained to become master criminals themselves. But now that life is behind her. Faced with the existence of a weapon that could threaten all life on Earth, M Freeman is ready to fight the good fight for a change. That means joining the Fulbright Academy. In their ancient cops-and-robbers conflict against the Lawless School, the Fulbrights are supposed to be the good guys. But the endless, winding subterranean hallways of the Academy hide many secrets. And M just can't resist a mystery. Is M a student or a prisoner? Can she and her friends really abandon their criminal ways to become champions of law and order? In a fast-paced, globe-spanning adventure, M and her crew follow the clues to one inescapable conclusion: It's time for M to take the law into her own hands" --